Ide hustle di era digital: Mengubah hobi menjadi sumber cuan yang stabil - Nisa, Nurul; Atiqa, Mira; Herlina H. (Jurnal Ekonomi dan Riset Pembangunan, 2026)
In the era of digital transformation, the boundaries between hobbies and economic activities have become increasingly blurred, triggering the side hustle phenomenon as a form of self-actualization and a source of income. This study aims to analyze the integration strategy between hobbies and digital technology to create a stable and sustainable income stream. Using a qualitative descriptive analysis approach, this research finds that the key to hobby-based economic stability lies in three main pillars: authentic personal branding development, product diversification, and the utilization of Artificial Intelligence (AI) for production efficiency. The discussion results show that although platform algorithms pose a challenge, the right digital tools can strengthen the resilience of micro-businesses. In conclusion, the transition from a hobbyist to a digital entrepreneur requires a balance between idealistic creativity and adaptive technological literacy